The facile synthesis, characterization and evaluation of photocatalytic activity of bimetallic FeBiO3 in natural sunlight exposure. Issue 124 (30th November 2015) - Aslam, M.; Soomro, M. Tahir; Ismail, Iqbal M. I.; Qari, Huda A.; Gondal, M. A.; Hameed, A.
Abstract : In an effort to develop sunlight active photocatalysts for environmental remediation, a phase pure bimetallic oxide, FeBiO3, was synthesized by a facile route. Abstract : In an effort to develop sunlight active photocatalysts for environmental remediation, a phase pure bimetallic oxide, FeBiO3, was synthesized by a facile route. The optical, structural and morphological properties of the synthesized FeBiO3 were compared with both the parent oxides i.e. α-Fe2 O3 and Bi2 O3 . The synthesized powder exhibited strong absorption in the visible region with the appearance of a distinct optical absorption edge at 2.15 eV. The PL, Raman and IR spectroscopic investigations of the synthesized powder, in comparison to that of pure oxides, confirmed the formation of pure phase FeBiO3 and revealed the dominant role of Fe 3+ ions in controlling the optical properties of the material. The X-ray diffraction analysis (XRD) revealed the hexagonal or rhombohedral geometry with an average crystallite size of 20.2 nm, whereas the X-ray photoelectron spectroscopy (XPS) verified the existence of both Fe and Bi in 3+ oxidation states. The electrochemical evaluation of the synthesized catalysts revealed its excellent stability in the neutral and basic pH in the dark and under illumination however, the catalyst was unstable in the harsh acidic medium (pH = 2). A low resistance to electron transfer and better charge retention ability was witnessed by EIS and chronopotentiometry. The photocatalytic activity of the synthesized catalysts was evaluated in the exposure of complete spectrum and visible region of natural sunlight for the removal of chemically stable substrates such as 2-nitrophenol and 2-chlorophenol. The catalysts showed considerably high activity for the removal of both the substrates in the exposure of natural sunlight, whereas 25% less activity was witnessed in visible region in the same span of time. In addition to degradation, the catalyst also exhibited a substantial activity for mineralization (TOC removal). The catalysts unveiled reproducible activity in the repeated scans. The chemical stability and sustained activity both in the complete spectrum and visible region designate it as a potential candidate for photocatalytic environmental remediation.